The use of algae to remove copper and lead from industrial wastewater - Cygnarowska, Katarzyna (Geology, Geophysics and Environment, 2023)
The aim of the research was to evaluate the effectiveness of the removal of Cu and Pb ions by algae. The experiments were carried out in the presence of two algal populations: a pure culture of Raphidocelis subcapitata, and a mixed chlorophyta population. The research involved a model study, experiments in the presence of wastewater from the manufacture of batteries, and the study of process kinetics. The wastewater pH was 4.0, and the initial concentrations of metal ions in the wastewater were 95.4 mg/L for Pb and 48.3 mg/L for Cu, respectively. The maximum sorption capacity of the pure Raphidocelis subcapitata culture was 14.8 mg/g d.m. for Pb, corresponding to the removal of 72% of lead, and 6.1 mg/g d.m. for Cu, corresponding to the removal of 43% of copper from the wastewater. The best ion sorption efficiency in the case of the mixed chlorophyta population was 7.0 mg/g d.m. for Pb, i.e., 61% removal of lead, and 12.8 mg/g d.m. for Cu, i.e., 69% removal of copper ions from the wastewater. The optimum duration of the process was found to be 1 hour, since the majority of biomass samples reached the maximum saturation after that time. On the basis of the obtained results (Lagergren models), it was found that the dominant mechanism of the process was chemisorption.